The Effect of Music on Working Memory Performance in Noisy Simulated Open-Plan Offices: An Experimental Study - Mostafa Mohammadian; Reza Kazemi; Sina Mollahoseini; Andy Smith (Journal of Health Sciences and Surveillance System)
Background: In open-plan office environments, irrelevant speech noise (ISN) is a common complaint among employees, leading to reduced performance. This study aimed to assess the impact of music on the working memory performance of individuals exposed to ISN in simulated open-plan offices. Additionally, we sought to examine any differential effects of music between male and female participants.Methods: In this experimental study, participants were selected through convenient sampling. Their working memory performance was evaluated using n-back (n=1, 2) tests conducted with software while they were exposed to irrelevant speech noise (ISN) alone and a combination of ISN and music. Sampling took place over one month during the spring season in the acoustic laboratory of the Faculty of Health in Shiraz, Iran.Results: Thirty students, including 15 females, with an ags range of 18 to 38 (Mean=25.27, Standard Deviation=6.03), participated in the study. The results showed a significant increase in the accuracy of participants’ responses to both simple and difficult tasks of the n-back (n=1, 2) test when music was played compared to the ISNonly condition. However, there was no significant difference between the conditions regarding reaction times in the working memory test.Conclusion: In the present study, the inclusion of music, specifically “For Elise,” emerged as a crucial factor in enhancing working memory amidst the presence of open-plan office noise. This finding underscores the potential of utilizing music as an effective strategy for improving cognitive performance in such environments. Given its cost-effectiveness and simplicity of implementation, incorporating background music like “For Elise” can be recommended as a favorable method for mitigating the negative impacts of noise in open-plan offices.